EUPHEMISMS REPRESENTING HIDDEN AND MYSTERIOUS CONCEPTS (Scientific journal of the Fergana State University, 2025)
This study explores the thematic categorization of euphemisms for societal vices in English, Russian, and Uzbek, focusing on their semantic features, cultural significance, and linguistic structures. A qualitative, descriptive methodology was employed, analyzing data from dictionaries, media texts, literature, and colloquial speech. Euphemisms were grouped into five thematic categories: substance abuse, prostitution, alcoholism, criminal activities, and corruption.The findings reveal that euphemisms are deeply influenced by cultural and linguistic contexts. English euphemisms often employ metaphors and idiomatic expressions, reflecting a more liberal approach to discussing sensitive topics. Russian euphemisms emphasize societal and moral undertones, balancing concealment and critique. Uzbek euphemisms are rooted in traditional values, emphasizing collective societal norms and moral judgments. These differences illustrate the diverse strategies used to address taboo topics across languages. The study concludes that euphemisms are essential tools for mitigating discomfort when discussing societal taboos and reflect cultural attitudes. Future research could explore the globalization of euphemisms and their adaptation in digital communication, offering valuable insights into evolving cross-cultural linguistic practices.